Keys to business longevity - Nyberg, Hanna (2020)
Why some companies fail before second generation while others survive through centuries is a fundamental puzzle for business research. Contradictory to most business sectors, the agricultural sector is characterized by being owned and driven by families over generations. For decades, research has posited knowledge as among the key factors for business longevity. Pursuing an aim to understand the phenomenon of organizational learning, this study takes its interest in the process of tacit knowledge creation and transfer. The empirical contribution is the stories and thoughts of farmers, regarding knowledge transfer over generations of the family farm business. Embracing the inherent complexity of real-world organizations, indepth interviews were conducted and analyzed with the aid from a conceptual framework constituted from two main literature areas within organization theory; family business and organizational learning.